Gambaran Jumlah Limfosit Pada Penderita Tuberkulosis Paru Yang Mendapat Terapi Obat Anti Tuberkulosis (OAT) Di Puskesmas Pekauman Kota Banjarmasin - Annisa Aprilia; Hajrah Hidriya; Risnawati Risnawati (UPPM Politeknik Unggulan Kalimantan, 2023)
Tuberculosis is a disease caused by Mycobacterium tuberculosis. These bacteria are transmitted from human to human through the air. Anti Tuberculosis Drug is the main strategy for controlling TB casses and lessening the chain of transmission. This study aims to determine the lymphocyte count of pulmonary tuberculosis patients who received Anti Tuberculosis Drug. This research used descriptive quantitative method with 23 respondents using venous blood as sample. Based on the results, the amount of respondent with normal lymphocytes were 21 respondents (91.3%), lymphopenia were 2 respondents (8.7%) and none had lymphocytosis (0%). For the results of lymphocytes count based on gender, 1 respondent (4.4%) had lymphopenia and 10 respondents (43.4%) were normal for the male, while for the female, 1 respondent (4.4%) had lymphopenia and 11 respondents (47.8%) were normal. Lymphocyte count results based on age, for productive age, 2 respondents (8.7%) had lymphopenia and 21 respondents (91.7%) were normal. The results of lymphocytes count based on the length of treatment, the intensive phase obtained 2 respondents (8.6%) with lymphopenia and 4 respondents (17.4%) were normal, for the continuation phase 17 respondents (74%) were normal.